Relationship Between Knowledge and Community Attitudes in First Aid to Traffic Accident Victims - Indri Wahyuningsih; Rina Sri Wahyuni Kurniawati; Indah Dwi Pratiwi; Risa Herlianita (PT FORMOSA CENDEKIA GLOBAL, 2022)
Many people who play an important role in providing first aid to traffic accident victims still prefer not to approach when an accident occurs. So that the purpose of this study is to analyze the relationship between knowledge and attitudes of the community in first aid to traffic accident victims. Methods: This research was conducted on 82 respondents who live close to Beji Highway, Beji Village, Junrejo District, Batu City from October 2020 to March 2021 using a correlation description design with a cross sectional approach. The instrument used is divided into 3 instruments with data collection tools in the form of a questionnaire consisting of demographic data, knowledge, and attitude questionnaires. The data collected were identified using the Spearman Correlation statistical test. Results: The majority of respondents have less knowledge (n=46, 56%) and have a negative attitude in first aid to traffic accident victims (n=81, 99%). Based on the results of the Spearman correlation test, the significance value (0.000) < (0.05) means that there is a relationship between knowledge and public attitudes in first aid for traffic accident victims with a moderate relationship strength (0.536) and a positive relationship direction, namely if knowledge increases the attitude of the people also increases. Conclusion: There is a relationship between knowledge and public attitudes in first aid to traffic accident victims.